Wildlife forensic science: A review of genetic geographic origin assignment. (September 2015) - Ogden, Rob; Linacre, Adrian
Highlights: Determining the geographic origin of evidence can support wildlife law enforcement. Modern DNA forensic approaches have the potential to resolve geographic origin. Geographic resolution may be increased through development of genome-wide non-neutral markers. The use and interpretation of assignment statistics requires the integration of genetic and life history data. Applications of genetic geographic origin assignment to forensics require further debate and standardisation. Abstract: Wildlife forensic science has become a key means of enforcing legislation surrounding the illegal trade in protected and endangered species. A relatively new dimension to this area of forensic science is to determine the geographic origin of a seized sample. This review focuses on DNA testing, which relies on assignment of an unknown sample to its genetic population of origin. Key examples of this are the trade in timber, fish and ivory and these are used only to illustrate the large number of species for which this type of testing is potentially available. The role of mitochondrial and nuclear DNA markers is discussed, alongside a comparison of neutral markers with those exhibiting signatures of selection, which potentially offer much higher levels of assignment power to address specific questions. A review of assignment tests is presented along with detailed methods for evaluating error rates and considerations for marker selection. The availability and quality of reference data are of paramount importance to support assignment applications and ensure reliability of any conclusions drawn. The genetic methods discussed have been developed initially as investigative tools but comment is made regarding their use in courts. The potential to compliment DNA markers with elemental assays for greater assignment power is considered and finally recommendations are made for the future of this type of testing.